Property, possession, incorporation: Another look at agribusiness venture agreements in the Philippines - Alfredo R. Rosete (University of Massachusetts, Department of Economics, 2016)
Of late, incorporating smallholder land, through partnerships with agribusiness firms that cultivate export crops has received some attention among scholars, policy- makers and non-government organizations (NGOs). Some see such partnerships as a means of raising smallholder incomes, and achieving rural development. However, several case studies have shown that such partnerships can result in low incomes, and effective dispossession of smallholders. This essay examines how this dynamic occurs by comparing the experiences of smallholders in the Davao Region of the Philippines. I argue that despite the smallholders observable and enforceable property rights, the costs and risks of cultivation, coupled with an unfavorable political environment generate conditions under which smallholders cede control over their holdings in a partnership. This results in both lower incomes, and exclusion from the use of their land.
Keywords: F63; N55; N75; O13; O19; O53; 330; Rural Development; Land Conflict; Agribusiness; Agrarian Reform June; 2016